Innovative Heat Exchangers (Springer International Publishing, 2018)
This accessible book presents unconventional technologies in heat exchanger design that have the capacity to provide solutions to major concerns within the process and power-generating industries. Demonstrating the advantages and limits of these innovative heat exchangers, it also discusses micro- and nanostructure surfaces and micro-scale equipment, and introduces pillow-plate, helical and expanded metal baffle concepts. It offers step-by-step worked examples, which provide instructions for developing an initial configuration and are supported by clear, detailed drawings and pictures. Various types of heat exchangers are available, and they are widely used in all fields of industry for cooling or heating purposes, including in combustion engines. The market in 2012 was estimated to be U$ 42.7 billion and the global demand for heat exchangers is experiencing an annual growth of about 7.8 %. The market value is expected to reach U$ 57.9 billion in 2016, and approach U$ 78.16 billion in 2020. Providing a valuable introduction to students and researchers, this book offers clear and concise information to thermal engineers, mechanical engineers, process engineers and heat exchanger specialists.